Platelet-to-lymphocyte ratio at the time of carotid endarterectomy is associated with acute coronary syndrome occurrence. Issue 1 (January 2020) - Bonaventura, Aldo; Carbone, Federico; Liberale, Luca; Mach, François; Roth, Aline; Burger, Fabienne; Pende, Aldo; Vecchié, Alessandra; Bertolotto, Maria; Spinella, Giovanni; Pane, Bianca; Palombo, Domenico; et al.
Abstract : Supplemental Digital Content is available in the text